Brain atrophy in natalizumab-treated patients: A 3-year follow-up. (May 2015) - Sastre-Garriga, J; Tur, C; Pareto, D; Vidal-Jordana, A; Auger, C; Río, J; Huerga, E; Tintoré, M; Rovira, A; Montalban, X
Background: A pseudoatrophy effect has been held responsible for the lack of net impact of natalizumab on brain volume outcomes in 2-year trials, but no data are available beyond 24 months. Objective: We aimed to investigate brain volume dynamics in natalizumab-treated patients in up to 3 years after therapy initiation with clinical correlations. Methods: Patients on natalizumab for at least 3 years were clinically assessed 3-monthly. Magnetic resonance imaging scans were performed at baseline and yearly. Brain volume changes were obtained with SIENA. Multivariate models were used to investigate the association between baseline inflammation and changes in brain volume and disability. Results: Sixty-two patients with multiple sclerosis were analysed. Mean age and disease duration were 34.7 (SD: 8.3) and 10.4 (SD: 6.6) years. Presence of gadolinium enhancement at baseline was not associated with Expanded Disability Status Scale changes ( p =0.468), but was associated with larger brain volume decreases ( p =0.005) in the first ( p =0.024) and second year ( p =0.019) but not in the third year ( p =0.863). Brain volume changes at 12 and 36 months were marginally associated with disability status at month 12 ( p =0.094) and 36 ( p =0.084), respectively. Conclusions: Baseline inflammation affects brain volume measures up to 24 months after natalizumab initiation. A marginal association of brain volume changes with disability is present.